On homotopy braids - Bardakov, Valeriy G. (Forum mathematicum)
The homotopy braid group (B) over cap (n) is the subject of the paper. First, the linearity of (B) over cap (n) over the integers is proved. Then we prove that the group (B) over cap (3) is torsion free.